A Critical Appraisal of Global Guidelines on Obturator Nerve Block in TURP: Urological and Anesthetic Collaboration: Penilaian Kritis terhadap Pedoman Global tentang Blok Saraf Obturator pada TURP: Kolaborasi Urologi dan Anestesi - Supardi, Alif Zulfikar; Reza, Muhammad Alfi; Krisna, Muhammad Sidharta; Wirawan, Nur Surya (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2025)
ABSTRACT Background: Obturator nerve block (ONB) is increasingly recognized as a crucial component in transurethral resection of the prostate (TURP) to prevent complications such as the obturator reflex, which can lead to intraoperative risks including bladder perforation. While ONB has been incorporated into various global clinical guidelines, its implementation remains inconsistent. Objective: This study critically examines the role of ONB in TURP by analyzing global guidelines, comparing different ONB techniques, and evaluating the integration of ONB with other surgical modalities to improve patient safety and procedural outcomes. Method: A comprehensive review of literature and clinical guidelines was conducted to assess the effectiveness, safety, and best practices related to ONB in TURP. Key parameters examined include the efficacy of ultrasound-guided ONB, multimodal approaches combining ONB with bipolar energy or laser techniques, and the impact of training programs for anesthesiologists. Results: Global guidelines from major urological and anesthesiology associations recommend ONB as a beneficial but non-mandatory procedure in TURP, particularly for high-risk patients. Evidence suggests that ultrasound-guided ONB improves procedural success rates and reduces complications. The combination of ONB with newer surgical modalities offers enhanced safety, and structured training programs can further facilitate its adoption in clinical practice. Conclusion: Although ONB is not universally required for TURP, its application significantly improves intraoperative safety. Standardizing protocols, expanding training programs, and integrating ONB with advanced surgical techniques can enhance the efficacy and reliability of TURP globally. Future research should focus on long-term outcomes and cost-effectiveness to refine clinical recommendations.